Design and Simulation of Novel 3-DOF Spherical Voice Coil Motor - Yi-Hsuan Lin; Chien-Sheng Liu; Chiu-Nung Yeh (Actuators, 2021)
Multi-DOF motion is realized in the eyes and joints of robots mostly through the combination of multiple one-degree-of-freedom (1-DOF) motors. However, this results in reduced efficiency, a large volume, reduced response speed, and inaccurate positioning. To solve these problems, this study proposes a novel 3-DOF spherical voice coil motor (VCM). In this VCM, 16 coils and a radially oriented ring magnet are used to generate a Lorentz force to achieve motion. In particular, coils for Z-axis rotation are sandwiched between the coils for X- and Y-axis rotation. Furthermore, the proposed VCM can achieve 360° rotation about the Z-axis. The commercial software ANSYS was used to design and verify the performance of the proposed VCM. Simulation results indicate that this VCM affords improved power efficiency because only a suitable combination of coils, rather than all coils, needs to be powered on. The results demonstrate the feasibility of the proposed 3-DOF spherical VCM.